Antifibrotic effects of roscovitine in normal and scleroderma fibroblasts. - Richard A Steinman; Andria Rasile Robinson; Carol A Feghali-Bostwick (PLoS ONE, 2012)
Heightened production of collagen and other matrix proteins underlies the fibrotic phenotype of systemic sclerosis (SSc). Roscovitine is an inhibitor of cyclin-dependent kinases that promote cell cycling (CDK1, 2), neuronal development (CDK5) and control transcription (CDK7,9). In an in vivo glomerulonephritis model, roscovitine treatment decreased mesangial cell proliferation and matrix proteins [1]. We investigated whether roscovitine could regulate fibrotic protein production directly rather than through cell cycling. Our investigations revealed that roscovitine coordinately inhibited the expression of collagen, fibronectin, and connective tissue growth factor (CTGF) in normal and SSc fibroblasts. This effect occurred on a transcriptional basis and did not result from roscovitine-mediated cell cycle inhibition. Roscovitine-mediated suppression of matrix proteins could not be reversed by the exogenous profibrotic cytokines TGF-β or IL-6. To our knowledge, we are the first to report that roscovitine modulates matrix protein transcription. Roscovitine may thus be a viable treatment option for SSc and other fibrosing diseases.